Root cause analysis of pinhole defects on painted galvanized steel panel. (September 2020) - Jin, Xinyan; Bi, Wenzhen; Wang, Li; Qian, Hongwei
Highlights: Dents on the base steel caused the bare spots on galvanized steel and further resulted in pinhole defects on painted panel. Coarse grains around the dents suggested its formation after primary recrystallization. Removing buildups on furnace rolls helped to eliminate pinhole defects. Abstract: Galvanized steel sheets have been widely used in automotive industries. However, it is still a challenge for steel makers to produce defect free hot dip galvanized steel sheets especially for outer panel applications in automotive body. In this study, the root cause of uncommon pinhole defects on painted hot dip galvanized steel panel was investigated. Optical microscopy (OM), scanning electron microscope (SEM) coupled with energy dispersive spectrometry (EDS), and auger electron spectroscopy (AES) were used to characterize these pinhole defects from top surface to base steel layer by layer. A reannealing experiment was carried out to reproduce the key features of the corresponding defect on the base steel. It was found that the pinhole defects were composed of a series of connected voids in the paint layers and started from the dents on the base steel prior to hot dip galvanizing. Based on the results of coarse grains around the dents and residual boron oxides at the dent bottom, further cause of the dents was attributed to the boron containing buildups on furnace rolls in the high temperature section of hot dip galvanizing line. As the surface of furnace rolls was cleaned up, the dent defects on the base steel, the bare spot defects in the zinc coating and the pinhole defects on the painted panel were eliminated successfully.